Contradictions of Agency, Educational Discourses, and Learner Changes: Mexican Women’s Enactments of Agency in Family Literacy and their Community - Blaire Willson Toso (Adult Education Research Conference, 2011)
This qualitative study explored Latina women’s use of hegemonic mothering and literacy discourses, encountered in an adult education and family literacy program. Findings revealed that participants were simultaneously constrained by and appropriated prevalent discourses to achieve goals or advance ideas that challenged normative views of women. Material and social structures also defined which and how participant goals could be pursued. Examining discourses and learner agency and constraints can assist educators and policy makers in better supporting learners to achieve their goals and to examine how social structures and hegemonic ideas shape learner lives, and expand understandings of discourses and agency.
Keywords: family literacy; immigrant; discourse; agency; mothering